2007
DOI: 10.1007/s10488-007-0151-x
|View full text |Cite
|
Sign up to set email alerts
|

Driving with Roadmaps and Dashboards: Using Information Resources to Structure the Decision Models in Service Organizations

Abstract: This paper illustrates the application of design principles for tools that structure clinical decision-making. If the effort to implement evidence-based practices in community services organizations is to be effective, attention must be paid to the decision-making context in which such treatments are delivered. Clinical research trials commonly occur in an environment characterized by structured decision making and expert supports. Technology has great potential to serve mental health organizations by supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 19 publications
0
101
0
Order By: Relevance
“…What is role play vs. in vivo rehearsal?) and making a template means of reporting this information is important particularly if it will inform a mechanism for tracking clinical progress and practice (Bickman, 2008a;Chorpita et al, 2008). Establishing integrity-promoting practices within supervision may be important as previous findings have indicated that adherence to supervisory principles can be related to therapist adherence to treatment principles (Schoenwald, Sheidow, & Chapman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…What is role play vs. in vivo rehearsal?) and making a template means of reporting this information is important particularly if it will inform a mechanism for tracking clinical progress and practice (Bickman, 2008a;Chorpita et al, 2008). Establishing integrity-promoting practices within supervision may be important as previous findings have indicated that adherence to supervisory principles can be related to therapist adherence to treatment principles (Schoenwald, Sheidow, & Chapman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A therapist's capacity to plan treatment and adjust intervention procedures appropriately during care can be enhanced by ongoing information about client response (e.g., Chorpita, Bernstein, & Daleiden, 2008;Lambert, Harmon, Slade, Whipple, & Hawkins, 2005;Weisz et al, 2004;Weisz & Chorpita, in press). Moreover, clients often unilaterally end treatment without notice and thus are unavailable for termination debriefing or post-treatment assessment.…”
Section: Youth Top Problemsmentioning
confidence: 99%
“…It is unclear how the clusters of discrete practices incorporated within these treatments translate to community settings (Wachtel, 2010). In recent efforts to implement evidence-based mental health treatments, Chorpita, Bernstein, and Daleiden (2008) and Chorpita, Daleiden, and Weisz (2005) have found it helpful to assess implementation of "lower level" practices, that is, the component interventions or practices covered in treatment manuals. They describe this method as distillation, "whereby interventions are conceptualized not as single units of analysis, but rather as composites of individual strategies, techniques, or components that can allow subsequent empirical grouping" (Chorpita et al, 2005, p. 6).…”
Section: Introductionmentioning
confidence: 99%